Mutational Analysis of the Rhodopsin Gene in Sector Retinitis Pigmentosa. (3rd July 2015) - Napier, Maria L.; Durga, Dash; Wolsley, Clive J.; Chamney, Sarah; Alexander, Sharon; Brennan, Rosie; Simpson, David A.; Silvestri, Giuliana; Willoughby, Colin E.
Abstract: Background : To determine the role of rhodopsin ( RHO ) gene mutations in patients with sector retinitis pigmentosa (RP) from Northern Ireland. Design : A case series of sector RP in a tertiary ocular genetics clinic. Participants : Four patients with sector RP were recruited from the Royal Victoria Hospital (Belfast, Northern Ireland) and Altnagelvin Hospital (Londonderry, Northern Ireland) following informed consent. Methods : The diagnosis of sector RP was based on clinical examination, International Society for Clinical Electrophysiology of Vision (ISCEV) standard electrophysiology, and visual field analysis. DNA was extracted from peripheral blood leucocytes and the coding regions and adjacent flanking intronic sequences of the RHO gene were polymerase chain reaction (PCR) amplified and cycle sequenced. Main Outcome Measure : Rhodopsin mutational status. Results : A heterozygous missense mutation in RHO (c.173C > T) resulting in a non-conservative substitution of threonine to methionine (p. Thr58Met) was identified in one patient and was absent from 360 control individuals. This non-conservative substitution (p.Thr58Met) replaces a highly evolutionary conserved polar hydrophilic threonine residue with a non-polar hydrophobic methionine residue at position 58 near the cytoplasmic border of helix A of RHO. Conclusions : The study identified a RHO gene mutation (p.Thr58Met) not previously reported in RP in a patient with sector RP. These findings outline the phenotypic variability associated with RHO mutations. It has been proposed that the regional effects of RHO mutations are likely to result from interplay between mutant alleles and other genetic, epigenetic and environmental factors.